Trace element concentrations, multivariate analysis and health risk potential of soils from urban and peri-urban agriculture - K.M. Hawrami; A.K. Baset (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES A rapidly increasing human population has resulted in the expansion of urban areas and an associated increase in the demand for food.  Consequently, urban and peri-urban agriculture, using waste water as a source for irrigation, is increasingly common around the world, particularly in developing countries.  In the Kurdistan region of Iraq, the soils within Agriculture areas have the potential to accumulate trace elements originating from various sources of contamination like municipal waste disposal and the use of wastewater for irrigation. The main aim of this study was to assess the levels and sources of trace elements in this specific region and to analyze the potential health hazards linked to toxic elements present in the soil.METHODS: Elemental analyses were conducted on soil samples using the total digestion method, involving the use of Hydrofluoric acid. Subsequently, 118 soil samples, each with a fraction size of less than 2 millimeters, were analyzed. These samples were collected from seven different urban and peri-urban agriculture areas in Sulaimani province. The analysis was carried out using Inductively coupled plasma mass spectrophotometry, which operated in collision cell mode with 7 percent hydrogen in helium to minimize polyatomic interferences.FINDINGS: The study findings indicated that the soils, with a potential hydrogen range of 7.5 to 8.18, are mainly calcareous and have textures that vary from silty loam to sandy or silty clay. Additionally, the organic matter content of these soils ranges from 1.4 percent to 5.47 percent. It was noted that soils subjected to wastewater irrigation do not show significant contamination by trace elements, whereas those affected by waste disposal sites showed high levels of chromium (134 milligrams per kilogram), copper (263 milligrams per kilogram), zinc (773 milligrams per kilogram), cadmium (4.19 milligrams per kilogram) and lead (161 milligrams per kilogram). Evaluation of enrichment factors indicates that the concentrations of trace elements generally remain within the anticipated background levels, with the exception of the municipal waste disposal site. The hazard indices derived for the trace elements indicate that the potential health risks associated with exposure routes are minimal. These indices consistently remain below the internationally recognized threshold of one, which signifies that the health concerns are insignificant fall within acceptable boundaries.CONCLUSION:  The concentrations of trace elements exhibited a notable increase in locations allocated for waste disposal, demonstrating a gradual decline in comparison to other agricultural regions. Throughout all the locations examined, the levels of nickel consistently remained elevated, suggesting that the geological attributes of the region have a significant impact.